2015
DOI: 10.1017/s1041610215000356
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict cognitive decline in patients with subjective cognitive impairment

Abstract: Patients who present with subjective memory complaints and are over the age of 61 years are at high risk of cognitive decline and warrant an in-depth assessment and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…This suggests that objective decline could be detected in those with SCD if more sensitive neuropsychological tests were applied. Consistent with this possibility, some studies have found that older adults with SCD have subtle changes in episodic memory, psychomotor speed, language or executive functions compared to those without SCD [22, 2527]; however, these subtle cognitive differences are very difficult to capture at the individual level [28], and potential mediating factors such as mood, personality characteristics, and cognitive reserve were not always ruled out in these studies [22]. Although several neuropsychological tests were used to measure objective cognitive performance in the present study, it is possible that a relationship with SCD may have been observed, even after accounting for the relationship between SCD and symptoms of depression, with more sensitive measures of cognition.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests that objective decline could be detected in those with SCD if more sensitive neuropsychological tests were applied. Consistent with this possibility, some studies have found that older adults with SCD have subtle changes in episodic memory, psychomotor speed, language or executive functions compared to those without SCD [22, 2527]; however, these subtle cognitive differences are very difficult to capture at the individual level [28], and potential mediating factors such as mood, personality characteristics, and cognitive reserve were not always ruled out in these studies [22]. Although several neuropsychological tests were used to measure objective cognitive performance in the present study, it is possible that a relationship with SCD may have been observed, even after accounting for the relationship between SCD and symptoms of depression, with more sensitive measures of cognition.…”
Section: Discussionmentioning
confidence: 87%
“…Third, we cannot address the value that SCD may hold in predicting future cognitive decline in this sample due to the cross-sectional nature of this study. Several research studies have observed minimal cross-sectional associations between SCD reporting and cognitive performance [5, 8, 9, 24], while others have consistently found associations between SCD reporting and biomarkers of Alzheimer’s disease and future cognitive decline [25, 3133], although this is not always the case [34, 35]. Our current results replicate and extend previous cross-sectional findings in non-Hispanic Whites to a group of Hispanic older adults; however, additional research continues to be needed to determine the value of SCD in predicting future cognitive changes in older Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies might take advantage of those markers, which may be better suited for study within larger samples that allow improved phenotypic (diagnostic) stratification. Furthermore, some clinical data indicates that SCI and MCI could be relatively close transitional states preceding AD515253, which may be reflected as similar brain dynamics in the two diagnoses. Although there were robust statistical associations, the lack of a healthy control group that had not been referred from the memory clinic may have limited the power to detect some MCI- and AD-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…Even though individuals with SCD, by definition, perform in the objective “normal” range on standard clinical assessments [2], they may demonstrate subtle clinical changes. For example, a few studies have identified objective weaknesses in memory [13,14] and executive functioning [15,16] in those with SCD. Another study of community-dwelling older adults found that difficulties in everyday functioning were commonly endorsed by participants who had a cognitive complaint [17].…”
Section: Introductionmentioning
confidence: 99%